Detection of gene mutations in genome “hot” spots: “hairpin” amplicons in DNA melting analysis - V. N. Kondratova; I. V. Botezatu; V. P. Shelepov; A. V. Lichtenstein (Успехи молекулярной онкологии, 2017)
Polymerase chain reaction (PCR) followed by DNA melting analysis with TaqMan probes effectively reveals mutations in the human genome “hot” spots. The necessity to carry out PCR in the asymmetric variant causes, however, a number of restrictions of this method: 1) an inability of quantitative estimates of gene copy numbers; 2) the need for 2 independent PCR tests for detection of mutations in both complementary strands of an amplicon (this approach improves reliability and sensitivity of the analysis); 3) the complication of PCR design and decrease in efficiency of amplification. Overcoming these restrictions was possible by means of symmetric PCR with primers containing the specific and universal sequences: the single-stranded “hairpins” (sense and antisense) are not capable to anneal with each other, but they can hybridize independently with 2 TaqMan probes present in the reaction mixture. The proposed approach allows quantitative and qualitative characterization of a DNA sample (the copy number estimates as well as mutation scanning of both complementary amplicon strands).